Emerging role of mesenchymal stem cells-derived extracellular vesicles in vascular dementia - Liu, Ziying; Cheng, Lin; Zhang, Lushun; Shen, Chunxiao; Wei, Shufei; Wang, Liangliang; Qiu, Yuemin; Li, Chuan; Xiong, Yinyi; Zhang, Xiaorong (Frontiers in Aging Neuroscience, 2024)
Vascular dementia (VD) is a prevalent cognitive disorder among the elderly. Its pathological mechanism encompasses neuronal damage, synaptic dysfunction, vascular abnormalities, neuroinflammation, and oxidative stress, among others. In recent years, extracellular vesicles(EVs) derived from mesenchymal stem cells (MSCs) have garnered significant attention as an emerging therapeutic strategy. Current research indicates that MSC-derived extracellular vesicles (MSC-EVs) play a pivotal role in both the diagnosis and treatment of VD. Thus, this article delves into the recent advancements of MSC-EVs in VD, discussing the mechanisms by which EVs influence the pathophysiological processes of VD. These mechanisms form the theoretical foundation for their neuroprotective effect in VD treatment. Additionally, the article highlights the potential applications of EVs in VD diagnosis. In conclusion, MSC-EVs present a promising innovative treatment strategy for VD. With rigorous research and ongoing innovation, this concept can transition into practical clinical treatment, providing more effective options for VD patients.